OPTION CHAIN DYNAMICS: ANALYSING OPEN INTEREST, TRADING VOLUME, AND LAST TRADED PRICE RELATIONSHIPS - Agarwal, Krishang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
This paper investigates the dynamic interplay between option chain metrics—specifically open interest (OI), trading volume, and last traded price (LTP)—within financial markets. Utilizing data spanning multiple market cycles, we explore how changes in these metrics influence one another and impact underlying asset prices. Drawing upon existing literature and empirical analysis, we seek to elucidate the predictive power of these indicators on market movements and volatility.